PENGARUH Governace GOOD CORPORATE TERHADAP NILAI PERUSAHAAN DENGAN RISIKO KREDIT SEBAGAI variabel intervening (Pada Perusahaan Perbankan Yang Terdaftar Di BEI) - Wayan Putri Lawinataliani (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This research is aimed at determining the direct and indirect effect of good corporate governance on the value of company with the credit risk as the intervening variable analyzing the financial performance of the bank registered in Indonesia Stock Exchange  during the period of 2011-2013. Good Corporate Governance is examined with the composite of GCG which is the self assessment of the bank. The credit risk is examined with the Non Performing Loan (NPL). The value of the company is examined with the Price Book Value (PBV). The number of the population of this research is 41 companies from which 22 samples were selected through purposive sampling. The analysis in this research is the path analysis to obtain the whole description of the correlation between one and another variable. The research showed that GCG has effect on the credit risk, while the credit risk has the effect on the company value. Thus this means that credit risk can be the intervening variable  between GCG and the company value.Key Words  : GCG, NPL dan PBV